(3GdQMdI Edi GfLdJQGs - (3CHh Ydj GdMSf Hf eMeO GdZSGd GdWfLj,J (B1358 (3g` s ((3KZQ WfLI s)
(3ChdgG (B:s
(3GdMeO ddg GdgGOi Edi ShGA GdWQjb hHYO , deG HdZ TQja Yde SjOfG CejQ GdeDefjf hehdGfG YHO GdYRjR LdGdI EOhGQO GdSGHY ef GdLdhS Ydi efUI GdYR s
(3BNQgG (B:s
(3hai GdSGYI GdKGdKI CbdY HfG eQcHg , hHYO SGYJjf hfUa hUdfG KZQfG GdSYjO hddg GdMeO GhdkG hBNQkG hNPG eG jSQ Gddg LeYg ai gPg GdhLgI GdejehfI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B25 - (3U(B42s
(3GdJgfFI EOhGQO GdSGHY edc EfLdJQG hGfJgi ef JHjVgG ai TgQ LeGOi GdKGfjI (B1320 (3g` cJHJ ef fSNI HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B222 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B589s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs